Cold mountain - Pollack, Sydney; Minghella, Anthony; Miramax Films (Burbank, CA : Miramax Home Entertainment : Distributed by Buena Vista Home Entertainment, 2004)
'At the dawn of the Civil War, the men of Cold Mountain, North Carolina, rush to join the Confederate army. Ada has vowed to wait for Inman, but as the war drags on and letters go unanswered, she must find the will to survive'
Title from title screen
Based on the novel by Charles Frazier
Director of photography, John Seale; production design, Dante Ferretti; editor, Walter Murch; score, Gabriel Yared
Casts : Jude Law, Nicole Kidman, Renée Zellweger, Eileen Atkins, Brendan Gleeson, Philip Seymour Hoffman, Natalie Portman, Giovanni Ribisi, Donald Sutherland
Keywords: Man-woman relationships -- Drama; Historical films; Soldiers -- Drama; United States -- History -- Civil War, 1861-1865 -- Drama